Thermal analysis of a partially ceramic coated piston: Effect on cold start HC emission in a spark ignition engine - Cerit, M.; Ayhan, V.; Parlak, A.; Yasar, H. (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
Effect of partially thermal barrier coating on piston temperature distribution and cold start HC emissions of a spark ignition (SI) engine are investigated numerically and experimentally. A Thermal analysis was performed for both standard and coated pistons by using a commercial code, namely ANSYS. The engine tests were conducted on a single cylinder, water cooled SI engine for both standard and coated cases. Analysis results show that the surface temperature of the coated piston part was increased up to 100 degrees C. which leads to an increase in air-fuel mixture temperature in the crevice and wall quenching regions. Thus, cold start HC emissions considerably decrease compared to the standard engine without any degradation in engine performance. Maximum decrease in HC emissions was 43.2% compared to the standard engine. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Thermal analysis; Finite element method; Spark ignition engines; HC emissions; Cold start; Thermal barrier coating; DIESEL-ENGINE; PERFORMANCE; RATIO; Thermodynamics; Energy & Fuels; Engineering; Mechanics